Quarantine Coleoptera pests of the genus Agrilus spp. - Vovkotrub, O.M.; Krivosheev, S.P. (Quarantine and plant protection, 2026)
Goal. To characterize the morphological and biological features of quarantine species of the genus Agrilus spp. and to determine the risks of their invasion in the European and Mediterranean Plant Protection Organization (EPPO) member countries and in Ukraine, by analogy with the emerald ash borer (Agrilus planipennis F.). Methods. Analysis of official data from the State Service of Ukraine on Food Safety and Consumer Protection and other official sources, including EPPO, using a bibliographic method. Results. The morphological and biological features of quarantine species of the genus Agrilus spp. were analyzed, including the presence of their host plants in the territories of EPPO member countries and Ukraine. The suitability of climatic conditions and the probability of acclimatization and spread of the pest in these territories were also investigated. Conclusions. A comparative analysis of the developmental characteristics of quarantine species of the genus Agrilus spp. and their environmental requirements indicates a high probability of acclimatization and adaptation in the territories of EPPO member countries, particularly in Ukraine. In the event of the introduction of these phytophagous insects into new territories, by analogy with Agrilus planipennis F., significant economic losses of host plants are expected due to damage caused by quarantine species of the genus Agrilus spp., as well as complications in control measures due to their concealed lifestyle.